Incomplete Inpatient Medical Record Documents at Hospital - Gamasiano Alfiansyah; Alvira Nafisah Eky Mulia; Rossalina Adi Wijayanti; Sabran Sabran (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The medical record contains the patient's identity, examination, treatment, actions and other services that have been provided to patients. There were incomplete integrated patient progress notes 61% and incomplete medical resumes 73%. The research intended to analyze the aspects that caused the incompleteness of inpatient medical record documents at the Besuki Hospital. This research used a qualitative method with data collection techniques interviews, observation dan documentation. The subjects in this study were 1 head of medical records and 5 medical record officers. The result showed that the factors causing the incompleteness of inpatient medical record documents from the motivational variable were that there was still no award and punishment for medical record officers. Opportunity variables were the absence of incomplete record cards, medical record officers who have never attended any training at all, SOPs for checking the completeness of medical records missing and having never been socialized. The ability variable was that there were medical record officers who did not have a minimum education of medical recorders, the knowledge of officers is still lacking and there were officers who had work experience of less than 2 years.Abstrak: Rekam medis berisi identitas pasien, pemeriksaan, pengobatan, tindakan dan pelayanan lain yang telah diberikan kepada pasien. Berdasarkan hasil observasi diketahui bahwa terdapat ketidaklengkapan CPPT sebesar 61% dan ketidaklengkapan resume medis sebesar 73%. Penelitian bertujuan untuk mengidentifikasi dan menganalisis penyebab ketidaklengkapan rekam medis rawat inap di RSUD Besuki. Jenis penelitian adalah kualitatif, pengumpulan data dilakukan dengan wawancara mendalam, dokumentasi, dan observasi. Subyek pada penelitian ini yaitu 1 ketua rekam medis dan 5 petugas rekam medis. Hasil penelitian menunjukkan faktor penyebab ketidaklengkapan dokumen rekam medis rawat inap dari variabel motivasi yaitu masih belum ada pemberian penghargaan dan hukuman untuk petugas rekam medis. Variabel kesempatan yaitu belum adanya kartu catatan ketidaklengkapan, petugas rekam medisbelum pernah mengikuti pelatihan sama sekali, SOP kegiatan pengecekan kelengkapan rekam medis hilang dan belum pernah disosialisasikan. Variabel kemampuan yaitu terdapat petugas rekam medis yang tidak memiliki pendidikan minimal D3 Rekam Medis, pengetahuan petugas rekam medis masih kurang dan ada petugas memiliki pengalaman kerja kurang dari 2 tahun.